2004
DOI: 10.1021/jf049389q
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antioxidant Effects of Milk Protein-Based Film Containing Essential Oils for the Preservation of Whole Beef Muscle

Abstract: Milk protein-based edible films containing 1.0% (w/v) oregano, 1.0% (w/v) pimento, or 1.0% oregano-pimento (1:1) essential oils mix were applied on beef muscle slices to control the growth of pathogenic bacteria and increase the shelf life during storage at 4 degrees C. Meat and film were periodically tested during 7 days for microbial and biochemical analysis. The lipid oxidation potential of meat was evaluated by the determination of thiobarbituric reactive substances (TBARS). The availability of phenolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
1
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(182 citation statements)
references
References 60 publications
6
155
1
11
Order By: Relevance
“…Another study reported 1.12 log reduction of E. coli O157:H7 populations in beef meat when coated with 1 % oregano essential oil (Oussalah et al 2004). Likewise, Mastromatteo et al (2009) also concluded that chicken meat quality can be enhanced by treating it with thyme and carvacrol at concentration of 300 ppm/kg meat.…”
Section: Essential Oils and Plant Extractsmentioning
confidence: 99%
“…Another study reported 1.12 log reduction of E. coli O157:H7 populations in beef meat when coated with 1 % oregano essential oil (Oussalah et al 2004). Likewise, Mastromatteo et al (2009) also concluded that chicken meat quality can be enhanced by treating it with thyme and carvacrol at concentration of 300 ppm/kg meat.…”
Section: Essential Oils and Plant Extractsmentioning
confidence: 99%
“…Whey protein isolate coatings containing antimicrobial agents like oregano EO, 3-polylysine, or sodium lactate were used on fresh beef under refrigeration, which was evaluated against the progression of microlora like Pseudomonas bacteria [91]. By using 1.5% of oregano EO or 0.75% of 3-poly-lysine, the growth of Pseudomonas spp.…”
Section: Antimicrobial Edible Coatingsmentioning
confidence: 99%
“…Similarly, chitosan coatings in combination with oregano oil at a concentration of 0.7% are used against Pseudomonas spp. and Brochothrix thermosphacta [91]. Gelatin ilms are used in Turkey bologna in combination with nisaplin-based ilms (GNF) (0.025-0.5%; w/v nisin) against L. monocytogenes bacteria [89].…”
Section: Antimicrobial Edible Coatingsmentioning
confidence: 99%
“…Oregano essential oil has been used in active packaging systems to protect foods from microbial contamination. Studies have shown that OEO in milk protein-based is highly effective against pathogen and spoilage bacteria even when compared with other EOs [47]. OEO not only helps control the growth of microorganisms but it can modify positively the characteristics of the bioactive film [48].…”
Section: Bioactive Filmsmentioning
confidence: 99%